Legal Protection For Wife As A Victim Of Domestic Violence Based On Law No. 23 Of 2004 On The Elimination Of Domestic Violence - Saniah Saniah (International Journal of Law and Society, 2025)
This study discusses domestic violence, especially against wives, after the issuance of Law No. 23 of 2004 concerning "Elimination of Domestic Violence.” This study aimed to determine the protection of wives as victims of domestic violence. The research method used was normative legal research, using primary, secondary, and tertiary legal materials. Library research was conducted to collect legal materials. The conclusion that can be put forward is that Law No. 23 of 2004 has normatively provided protection to victims or wives, but it is still not comprehensive, and there are still forms of protection that require more detailed explanation or description.